Digital Leadership, Teacher Stress, Engagement, and Innovation Effects on Xaverius Foundation Performance in Sumatra - Hendra, Robi; Habibi, Akhmad; Yovinda, A. Noven (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
The purpose of this research is to examine the relationship between digital leadership, educational innovation, and stress in the workplace as they pertain to teachers' performance, with employment engagement serving as a mediator. A total of 301 instructors from around the Sumatra region participated in this study, which was funded by the Xaverius Foundation. The data collection technique was carried out through a survey using a closed questionnaire based on a Likert scale of 1–5, with instruments that had been validated and translated into Indonesian using the back-translation method. The methodology employed is a quantitative approach that employs the SEM-PLS analysis tool. Educational innovation and teacher performance are both impacted by digital leadership, according to the research. In the model of linkages between factors, work engagement is the key mediating variable and has the strongest influence on teacher performance. In fact, research has shown that stress in the workplace has no discernible effect on educators' productivity in the classroom. According to these results, innovation and leadership are not the only factors that contribute to better teacher performance; the level of engagement that teachers feel in their job also plays a major role. Hence, effective measures to improve teacher performance and assist relevant educational transformation in the digital era include generating planned educational innovations, boosting digital leadership, and promoting work engagement and stress management.